Cardioprotective Activity of Pharmacological Agents Affecting NO Production and Bioavailability in the Early Postnatal Period after Intrauterine Hypoxia in Rats - Popazova, O. O.; Belenichev, I. F.; Bukhtiyarova, N. V.; Ryzhenko, V. P.; Oksenych, V.; Kamyshny, О. M.; Попазова, Олена Олександрівна; Бєленічев, Ігор Федорович; Бухтіярова, Ніна Вікторівна; Риженко, Віктор Павлович; Камишний, Олександр Михайлович (My University, 2023)
Abstract: Intrauterine hypoxia in newborns leads to a multifaceted array of alterations that exert a detrimental impact on the cardiovascular system. The aim of this research was to assess the cardioprotective effects of modulators of the nitric oxide (NO) system, including L-arginine, Thiotriazoline, Angiolin, and Mildronate, during the early postnatal period following intrauterine hypoxia. Methods: The study involved 50 female white rats. Pregnant female rats were given a daily intraperitoneal dose of 50 mg/kg of sodium nitrite starting on the 16th day of pregnancy. A control group of pregnant rats received saline instead. The resulting offspring were divided into the following groups: Group 1—intact rats; Group 2—rat pups subjected to prenatal hypoxia (PH) and daily treated with physiological saline; and Groups 3 to 6—rat pups exposed to prenatal hypoxia and treated daily from the 1st to the 30th day after birth. Nitrotyrosine levels, eNOS, iNOS, and NO metabolites were evaluated using ELISA; to measure the expression levels of iNOS mRNA and eNOS mRNA, a PCR test was utilized. Results: Angiolin enhances the expression of eNOS mRNA and boosts eNOS activity in the myocardium of rats with ischemic conditions. Arginine and particularly Thiotriazoline exhibited a consistent impact in restoring normal parameters of the cardiac nitroxidergic system following PH. Mildronate notably raised iNOS mRNA levels and notably reduced nitrotyrosine levels, providing further support for its antioxidative characteristics.
Keywords: prenatal hypoxia; cardioprotective; heat shock proteins; Angiolin; L-arginine; Thiotriazoline; Mildronate; eNOS; iNOS; nitrotyrosine